Reverse Innovation Reconceptualised: Much Geo-Economic Ado about Primary Market Shift - Radojević, Nebojša (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
Present concept of reverse innovation urges multinational enterprises from developed countries to innovate for emerging markets, and to subsequently diffuse the outcome back to their home countries. The concept hence appears exclusively reserved for enterprises of particular size or origin, and for specific host countries or levels of development. This paper repositions the concept relatively to any enterprise’s dominant innovation logic, rather than relatively to its geo-economic environment. Reverse innovation thus becomes a template that any enterprise innovating for a new primary market abroad may customise to its specific situation regarding exogenous distances, endogenous distances, and managerial response.